BET Bromodomain Inhibitor iBET151 Impedes Human ILC2 Activation and Prevents Experimental Allergic Lung Inflammation - Kerscher, Bernhard; Barlow, Jillian L.; Rana, Batika M.; Jolin, Helen E.; Gogoi, Mayuri; Bartholomew, Michelle A.; Jhamb, Deepali; Pandey, Ashutosh; Tough, David F.; van Oosterhout, Antoon J. M.; McKenzie, Andrew N. J. (Frontiers in Immunology, 2019)
Abstract Group 2 innate lymphoid cells (ILC2) increase in frequency in eczema and allergic asthma patients, and thus represent a new therapeutic target cell for type-2 immune-mediated disease. The bromodomain and extra-terminal (BET) protein family of epigenetic regulators are known to support the expression of cell cycle and pro-inflammatory genes during type-1 inflammation, but have not been evaluated in type-2 immune responses. We isolated human ILC2 and examined the capacity of the BET protein inhibitor, iBET151, to modulate human ILC2s activation following IL-33 stimulation. iBET151 profoundly blocked expression of genes critical for type-2 immunity, including type-2 cytokines, cell surface receptors and transcriptional regulators of ILC2 differentiation and activation. Furthermore, in vivo administration of iBET151 during experimental mouse models of allergic lung inflammation potently inhibited lung inflammation and airways resistance in response to cytokine or allergen exposure. Thus, iBET151 effectively prevents human ILC2 activation and dampens type-2 immune responses.